The Activities on Prevention of Malaria and Filariasis Vector Bites among Indonesian Society: A Nationwide Disease Prevention Survey - Widawati, Mutiara; Ipa, Mara; Astuti, Endang Puji; Wahono, Tri; Yuliasih, Yuneu (Institute of Topical Disease Universitas Airlangga, 2022)
Vector Borne Diseases are diseases that cause many problems. These diseases are spread by mosquitoes as the vectors. They transmit parasites to humans through their bites. The people who live in Indonesia have several characteristics that make them vulnerable to these diseases. Therefore, it is necessary to explore these characteristics in order to gain better prevention promotional targeting strategy. This study aims to determine the factors that can influence mosquito bite prevention behaviour in Indonesian society. The data from a nationwide survey research were used with a cross sectional design conducted once in every five years. The Riskesdas was conducted from April to May 2018 in all districts in Indonesia. The influencing factors observed were including experience of exposure to vector borne diseases (malaria or filariasis), gender, age group, education level and area of residence. This study conducted a multivariate test using logistic regression analysis to determine the factors that influence mosquito bite prevention behaviour. The results demonstrated that the factors of experience of exposure to vector borne diseases, gender, age group, education level and area of residence could determine the mosquitoes bite prevention behaviour in Indonesian society. Respondents who have experience of being exposed to malaria or filaria, under 60 years old, women, college graduates, and rural communities are more likely to prevent mosquito bites, therefore they could be empowered in promoting public awareness towards mosquito bites prevention.